Development of Generation Z's Soft Skills (A Case Study of Extracurricular Activities - Deona, Salsabila; Solfema, Solfema (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2025)
This study explores the development of Generation Z’s soft skills through extracurricular activities, specifically the Teaching Factory (TEFA) TKI program at SMK SMTI Padang. Using a qualitative case study approach, data were collected through observation, interviews, and documentation. The research reveals that soft skills such as communication, leadership, critical thinking, problem-solving, curiosity, collaboration, and creativity are effectively developed through three main activities: product production challenges, entrepreneurship practice, and exhibition participation. Project-based learning (PJBL) is applied as the instructional model, supported by structured learning resources such as instructors and handouts. Learning environments include the school laboratory and the surrounding community, both of which provide real-life contexts to reinforce discipline, responsibility, adaptability, and interpersonal skills. Evaluation is conducted daily and at the end of the program, focusing on technical skills and personal development. The results demonstrate that well-designed extracurricular programs can be a powerful tool for enhancing students' soft skills, equipping Generation Z with the capabilities to face the uncertain demands of the digital era and competitive work environment. This study highlights the urgency of integrating soft skill development into non-formal educational programs to complement academic achievements and prepare students for the future.